STRATEGI PENINGKATAN KEUNGGULAN KOMPETITIF SDM BIDANG TIK DI ERA MEA - Setiadi, Ahmad (Universitas Bina Sarana Informatika, 2016)
ASEAN Economic Community (AEC) went into effect in 2015. Indonesia inevitablyrequired to be ready to deal with it, especially the readiness in the field of humanresources (HR). Facing regional competitions throughout the ASEAN region,Indonesian Human Resource Information and Communication Technology (ICT) isrequired to have a competitive advantage compared to human resources from othercountries. Therefore, it takes appropriate strategies to enhance the competitiveadvantage of the human resources in view of human resources in the ICT field has aspecial character. With the strategy to enhance the right competitive advantage,Indonesian human resources in ICT is expected to compete in this era of MEA.